2021
DOI: 10.1002/jbt.22922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of m6A methyltransferase METTL3 ‐mediated MALAT1/E2F1/AGR2 axis on adriamycin resistance in breast cancer

Abstract: N6-methyladenosine (m6A) methyltransferase METTL3 has been implicated in carcinogenesis, which may be associated the overexpression of MALAT1. However, the downstream mechanics actions remain largely unknown. This study intends to probe the downstream mechanism of the N6-methyladenosine (m 6 A) methyltransferase METTL3 and MALAT1 in adriamycin resistance in breast cancer. Through Bioinformatics databases lncMAP, TCGA and GTEx, we predicted the downstream transcription factors E2F1 and AGR2 of MALAT1 in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…METTL3 targeted MALAT1/miR-26b/HMGA2 axis and caused EMT and promotion of migration and invasion in breast cancer ( 50 ). METTL3 regulated MALAT1/E2F1/AGR2 pathway and subsequently controlled Adriamycin resistance in breast cancer ( 51 ). We also found that METTL3 controlled the expression of MALAT1 in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 targeted MALAT1/miR-26b/HMGA2 axis and caused EMT and promotion of migration and invasion in breast cancer ( 50 ). METTL3 regulated MALAT1/E2F1/AGR2 pathway and subsequently controlled Adriamycin resistance in breast cancer ( 51 ). We also found that METTL3 controlled the expression of MALAT1 in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latest study revealed the potential function of METTL3 in adriamycin resistance (ADR) in BC. METTL3-mediated m 6 A regulated MALAT1 expression, thereby recruiting E2F1 and promoting AGR2 expression, which resulted in ADR in BC [ 127 ]. A recent study in GC showed that the reader IGF3BP1 recognized METTL3-mediated m6A modification on apoptotic protease-activating factor 1-binding lncRNA to maintain its stability, which inhibited GC cell apoptosis and led to multidrug resistance [ 147 ].…”
Section: Targeting the M 6 A Modification To Surmo...mentioning
confidence: 99%
“…METTL3 was demonstrated to upregulate PD-L1 expression via IGF2BP3 by m 6 A-dependent manner to modulate immune surveillance in breast cancer ( Wan et al, 2022 ). The high level of METTL3 induced EMT, invasion and migration by targeting MALAT1/miR-26b/HMGA2 axis ( Li et al, 2022 ). DROSHA RNase III was upregulated in a number of cancers and interacted with β-catenin to activate stanniocalcin 1 (STC1) in an RNA cleavage-independent manner, which in turn contributed to the properties of breast cancer stem-like cells (BCSCs).…”
Section: Roles Of the Ribonucleic Acid Modification In The Carcinogen...mentioning
confidence: 99%
“…S-adenosylhomocysteine (SAH) can be hydrolyzed to produce adenosine (adenine) and homocysteine, which can inhibit cellular methyltransferase activity through substrate inhibition, and regulates transmethylation through inhibition of METTL3-METTL14 activity ( Eckert et al, 2019 ). The expression of MALAT1 was shown to be enhanced by METTL3 through recruitment of E2F transcription factor 1 (E2F1), resulting in transcription of anterior gradient 2 (AGR2), and subsequent adriamycin resistance in breast cancer ( Li et al, 2022 ). In a further study, METTL3 also promoted maturation of miRNA-221-3p in an m 6 A-dependent manner, which negatively regulated HIPK2, upregulated the target gene Che-1, and induced chemoresistance of breast cancer cells to doxorubicin ( Pan et al, 2021 ).…”
Section: Ribonucleic Acid Modifications As Potential Drug Targets In ...mentioning
confidence: 99%